Pengaruh Financial Knowledge, Financial Attitude, Personlity dan Demographics terhadap Financial Behavior (Studi Kasus UMKM Makanan dan Minuman di Kecamatan Tulangan Kabupaten Sidoarjo) - Islamiyah, Izzatul; Zaki, Achmad; Mustaqim, M; Violita, Cynthia Eka (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to determine partially and simultaneously the influence of financial knowledge, financial attitude, personality and demographics on financial behavior in Food and Beverage MSMEs in Tulangan District, Sidoarjo Regency. These factors are considered important in determining how business actors manage their finances, both in financial planning, budgeting, and investment decision making. The approach used in this study is quantitative, with the Partial Least Squares PLS method to analyze the relationship between variables. Data were collected through a questionnaire with a Likert scale and tested for validity and reliability before multiple linear regression analysis was carried out. The results of the study showed that financial knowledge, financial attitude, personality, and demographics had a significant effect on financial behavior. Financial knowledge plays a role in increasing the understanding of MSME actors in managing their business finances. A positive financial attitude is correlated with saving habits and financial risk management. Personality, especially individuals with a good level of self-control, tend to be more disciplined in managing their finances. Meanwhile, demographics, such as gender and education level, also play a role in shaping wiser financial behavior.